The Critical Role and Contribution of Transformational Leadership on the Achievement of Plenary Health Service: Scoping Review - Marterasari, Intani Fiska; Dwiantoro, Luky; Anggorowati, Anggorowati (GLOBAL HEALTH SCIENCE GROUP, 2024)
The quality of health services depends on the quality of human resources within the health facility.Developing a positive work atmosphere, boosting nurses' productivity, and guaranteeing effective nurse leadership is essential for delivering high quality nursing care services. The scope of the important role and contribution of transformational leadership to the achievement of complete health services.Method.Database search using CINAHL was conductedto locate pertinent Medical topic Headings (MeSH) and keywords found in the relevant literature's titles, abstracts, and topic descriptions. The scope of transformational leadership in the managerial process has 7 aspects, the elements involved in the implementation of transformational leadership have 5 aspects and the contribution of outcomes to patient safety in health services has 4 aspects. The scope of the review conducted include several classifications of aspects that are grouped, namely on the contribution of transformational leadership to the managerial process, the elements involved in the implementation of transformational leadership and the contribution of outcomes to patient safety in health services.